Hubungan Aktivitas Fisik dengan Kesehatan Mental pada Remaja - I Gusti Ayu Putu Satya Laksmi; Desak Made Ari Dwi Jayanti (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2023)
The period of growth and development in adolescence is characterized by neurodevelopment, identity formation, and behavioral patterns that can increase or decrease mental health. Mental health is very important to support productivity and quality of physical health. Mental health must be maintained both physically and mentally, currently more attention is given, both to adults and even teenagers, including groups who are prone to mental disorders or mental disorders that are quite high. One of the prevention strategies to reduce the possibility of mental health disorders is to do physical activity. The objectives of the study was to determine the relationship between physical activity and mental health of adolescents. The type of research used is correlational research with a cross sectional approach. The population in this study were adolescents aged 10-19 years. The sample in this study were all teenagers in Central Banjar, a total of 114 teenagers. Univariate analysis with frequency distribution and bivariate analysis with Spearman rank. The measuring instruments used to assess are physical activity questionnaires (International Physical Activity Questionnaire (IPAQ)) and mental health (The Mental Health Continuum-Short Form (MHC-SF)). The results showed that most of the adolescents included in the high physical activity category as many as 60 adolescents (52.6%) and included in the mental healthy category as many as 74 adolescents (64.9%). The results of the bivariate test with the Spearman Ranks test obtained a p value of 0.001 (p <0.05). The conclusion of this study is that there is a significant relationship (p = 0.001) between physical activity and adolescent mental health. Based on the results of this study, so that further researchers can identify specifically the type of physical activity that is most effective and effective time in carrying out activities that can affect mental health in adolescents. Keywords: physical activity, mental health, adolescents